Changes in primary metabolism under light and dark conditions in response to overproduction of a response regulator RpaA in the unicellular cyanobacterium Synechocystis sp. PCC 6803 - Iijima, Hiroko; Shirai, Tomokazu; Okamoto, Mami; Kondo, Akihiko; Hirai, Masami Yokota; Osanai, Takashi (Frontiers in Microbiology, 2015)
The study of the primary metabolism of cyanobacteria in response to light conditions is important for environmental biology because cyanobacteria are widely distributed among various ecological niches. Cyanobacteria uniquely possess circadian rhythms, with central oscillators consisting from three proteins, KaiA, KaiB, and KaiC. The two-component histidine kinase SasA/Hik8 and response regulator RpaA transduce the circadian signal from KaiABC to control gene expression. Here, we generated a strain overexpressing rpaA in a unicellular cyanobacterium Synechocystis sp. PCC 6803. The rpaA-overexpressing strain showed pleiotropic phenotypes, including slower growth, aberrant degradation of an RNA polymerase sigma factor SigE after the light-to-dark transition, and higher accumulation of sugar catabolic enzyme transcripts under dark conditions. Metabolome analysis revealed delayed glycogen degradation, decreased sugar phosphates and organic acids in the tricarboxylic acid cycle, and increased amino acids under dark conditions. The current results demonstrate that in this cyanobacterium, RpaA is a regulator of primary metabolism and involved in adaptation to changes in light conditions.